Rattus fuscipes ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
718. Australian Bush Rat Rattus fuscipes French: Rat de brousse / German: Australische SchwarzfulRratte / Spanish: Rata peluda de Australia Other common names: Allied Rat, Bush Rat; Western Swamp Rat (fuscipes), Southern Bush Rat (assimilis) Taxonomy. Mus fuscipes Waterhouse, 1839, “Australia, King George’s Sound.” Restricted by J. M. Taylor and B. E. Horner in 1973 to “ ‘Little Grove’ on Princess Royal Harbour, approx. 4 mi [= 6 km] south of Mount Melville, Albany, Western Australia, Australia.” Rattus fuscipes is sister to all other Australian Rattus except R. leucopus, which is basal to this clade. Each of the recognized subspecies is morphologically and genetically distinct; although they can interbreed, they might may represent distinct species (especially coracius) with further research. Rattus f. assimilis might represent multiple subspecies. Four subspecies recognized, but subspecific taxonomy requires reassessment. Subspecies and Distribution. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 848-849, DOI: 10.5281/zenodo.6887260 ...